1998
DOI: 10.1111/j.1348-0421.1998.tb02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Immunological Characterization of a Low Molecular Weight Outer Membrane Protein of Salmonella typhi

Abstract: A new immunogenic outer membrane protein, Omp-28 (MW 28,000 and pI 4.6), was isolated from smooth Salmonella typhi cells by the use of an extracting medium containing 6 M urea, I% deoxycholate and 5 mM EDTA. The purification of Omp-28 was performed by gel filtration and fast ion exchange chromatography. This protein showed to be the prevalent component isolated by the latter methodology. Omp-28 is formed by three identical subunits (MW 9,000), not linked by disulfide bonds. The partial N-terminal amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Typhi cells in serum dilution of 1/80 and 1/320. [17] Complete amino acid sequence and location of Omp 28 of S .Typhi has also been analysed. [18] As it is difficult to isolate Omp(s) in bulk for vaccine purpose, this study was undertaken to clone and sequence and in silico analysis of Omp 28 gene of S .Typhi to further explore the possibility of r-DNA vaccine of S .Typhi.…”
Section: Introductionmentioning
confidence: 99%
“…Typhi cells in serum dilution of 1/80 and 1/320. [17] Complete amino acid sequence and location of Omp 28 of S .Typhi has also been analysed. [18] As it is difficult to isolate Omp(s) in bulk for vaccine purpose, this study was undertaken to clone and sequence and in silico analysis of Omp 28 gene of S .Typhi to further explore the possibility of r-DNA vaccine of S .Typhi.…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that though the mortality was reduced after the vaccination with Omp 28 but Omp 28 could not provide complete protective immunity. First report on Omp 28 indicated that the level of antibodies against Omp 28 was very high in serum of collected from patients of typhoid [ 13 ]. Further, mice antibody raised against Omp 28 in mice showed anti-salmonella activity [ 14 ] in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Omp 28 is which had been purified from Salmonella Typhi. It was further sequenced, and few tests had been conducted to assess its immune potential in which it had exhibited promising potential [ 13 , 14 ]. Therefore, in our earlier study, we targeted Omp 28 as rDNA vaccine against S .…”
Section: Introductionmentioning
confidence: 99%